Decreased expression of gastric gland mucin‐specific glycan α1, 4‐linked N‐acetylglucosamine on its scaffold mucin 6 is associated with malignant potential of pyloric gland adenoma of the stomach. Issue 6 (8th July 2015) - Yamanoi, Kazuhiro; Sekine, Shigeki; Higuchi, Kayoko; Kushima, Ryoji; Nakayama, Jun
Abstract : Aims: Pyloric gland adenoma (PGA) is a unique gastric neoplasm expressing mucin 6 (MUC6), and is often associated with high‐grade dysplasia and/or adenocarcinoma. MUC6 secreted from the gastric gland mucous cells, such as pyloric gland cells, carries unique O ‐glycans with terminal α1, 4‐linked N ‐acetylglucosamine (αGlcNAc) residues on its molecule. As we recently demonstrated that αGlcNAc serves as a tumour suppressor for gastric adenocarcinoma, this study aimed to investigate the significance of αGlcNAc expression in PGA. Methods and results: Eighteen patients with PGA were examined with immunohistochemistry for αGlcNAc and MUC6. αGlcNAc and MUC6 were coexpressed in 12 of 18 PGAs. However, reduced αGlcNAc expression relative to MUC6 expression was observed in six cases. When the MIB‐1 labelling index (LI) of tumour cells was examined with respect to reduced αGlcNAc expression, the MIB‐1 LI was significantly higher in PGAs showing decreased αGlcNAc expression relative to MUC6 expression than in PGAs with unchanged αGlcNAc expression ( P = 0.023). Conclusions: The present study indicates that coexpression of αGlcNAc and MUC6 in PGA suggests the presence of fully glycosylated MUC6 on tumour cells, consistent with pyloric gland differentiation. However, the decreased glycosylation of αGlcNAc on MUC6 is associated with high mitotic activity of tumour cells, indicative of malignant potential of PGA.